Differential benefits of steroid therapies in adults following major burn injury. Issue 8 (August 2022) - Altarrah, Khaled; Tan, Poh; Acharjee, Animesh; Hazeldine, Jon; Torlinska, Barbara; Wilson, Yvonne; Torlinski, Tomasz; Moiemen, Naiem; Lord, Janet M
Abstract: Background: Major thermal injury induces a complex pathophysiological state characterized by burn shock and hypercatabolism. Steroids are used to modulate these post-injury responses. However, the effects of steroids on acute post-burn outcomes remain unclear. Methods: In this study of 52 thermally injured adult patients (median total burn surface area 42%, 33 males and 19 females), the effects of corticosteroid and oxandrolone on mortality, multi-organ failure (MOF), and sepsis were assessed individually. Clinical data were collected at days 1, 3, 7, and 14 post-injury. Results: Twenty-two (42%) and 34 (65%) burns patients received corticosteroids and oxandrolone within the same cohort, respectively. Following separate analysis for each steroid, corticosteroid use was associated with increased odds of in-hospital mortality (OR 3.25, 95% CI: 1.32–800), MOF (OR 2.36, 95% CI: 1.00–1.55), and sepsis (OR 5.95, 95% CI: 2.53–14.00). Days alive (HR 0.32, 95% CI: 0.18–0.60) and sepsis-free days (HR 0.54, 95% CI: 0.37–0.80) were lower among corticosteroid-treated patients. Oxandrolone use was associated with reduced odds of 28-day mortality (OR 0.11, 95% CI: 0.04–0.30), in-hospital mortality (OR 0.19, 95% CI: 0.08–0.43), and sepsis (OR 0.24, 95% CI: 0.08–0.69). Days alive, at 28 days (HR 6.42, 95% CI: 2.77–14.9) and in-hospital (HR 3.30, 95% CI: 1.93–5.63), were higher among the oxandrolone-treated group. However, oxandrolone was associated with increased MOF odds (OR 7.90, 95% CI: 2.89–21.60) and reduced MOF-free days (HR 0.23, 95% CI: 0.11–0.50). Conclusion: Steroid therapies following major thermal injury may significantly affect patient prognosis. Oxandrolone was associated with better outcomes except for MOF. Adverse effects of corticosteroids and oxandrolone should be considered when managing burn patients.